ANALYSIS OF BENDING MECHANICAL PERFORMANCE OF WELDING JOINTS WITH THE ADDITION OF DIAMOND AND CIRCULAR PLATES - Gatot Prayogo; Muhammad Arif Budiyanto; Mustasyar Perkasa (Indonesian Journal of Engineering and Science, 2023)
The design and analysis of welded joints are very useful for the safety of steel-based structures. The effect of welded joints meeting at one point on the resulting stress is a critical factor in constructing steel joints. The main objective of this research is to analyze the mechanical performance and microstructure of the welding process on diamond and circular plate joints. The analysis was carried out through experiments and finite element simulations to find out how much influence the addition of a diamond plate and circular plate had on the plate connection. The method used is to analyze the strength, hardness, and micro and macrostructure testing to determine the strength and structural changes of the metal after welding. The results of the test are then used to create an inhomogeneous model of weld joint, then the model is applied to the FEA software to be analyzed by the bending test simulation. The experimentally bending testing was carried out to examine bending performance of the test objects. From the simulation and experimental results, it is found that the shape of a circular plate measuring a diameter of 60 mm with a thickness of 6 mm is appropriate for a flat plate joint, and the flat-diamond plate measuring 60x60 mm with a thickness of 6 mm is proper for application to un-flat (cornered) plate joints. The structural integrity of a flat plate joint with a circular plate is greater than that of a diamond plate.